2008
DOI: 10.1002/hep.21987
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic cholestasis of pregnancy: Amelioration of pruritus by UDCA is associated with decreased progesterone disulphates in urine

Abstract: Intrahepatic cholestasis of pregnancy (ICP) is characterized by pruritus, elevated bile acids, and, specifically, elevated disulphated progesterone metabolites. We aimed to study changes in these parameters during treatment with dexamethasone or ursodeoxycholic acid (UDCA) in 40 out of 130 women included in the Swedish ICP intervention trial (26 randomized to placebo or UDCA, 14 randomized to dexamethasone). Serum bile acid profiles and urinary steroid hormone metabolites were analyzed using isotope-dilution g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
67
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 28 publications
1
67
0
5
Order By: Relevance
“…(3) In the 1990s, a series of reports centered in Sj€ ovall's laboratory, in Stockholm, Sweden, using now more sophisticated and precise techniques applied to serum and urine from Chilean patients with ICP and their controls, clarified that a distinctive biochemical feature in ICP was the switch of progesterone metabolism toward a four-fold to 10-fold increase in serum and urine concentration of sulfated metabolites, with an increased ratio of 3a-hydroxysteroid sulfates to 3b-hydroxysteroid sulfates, changes that were reversed after treatment with ursodeoxycholic acid. (4) Among other important steps in this research line, Glantz et al, in Sweden, reported similar changes in the pattern of progesterone metabolites in urine of ICP patients, with a reversal after ursodeoxycholic acid administration, correlating with an improvement in maternal pruritus (5) ; and Abu-Hayyeh et al also reported increased levels of progesterone sulfates in ICP patients studied in the United Kingdom. (6) Therefore, this metabolic pattern has been detected in ICP patients from different geographic locations and ethnic origins.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…(3) In the 1990s, a series of reports centered in Sj€ ovall's laboratory, in Stockholm, Sweden, using now more sophisticated and precise techniques applied to serum and urine from Chilean patients with ICP and their controls, clarified that a distinctive biochemical feature in ICP was the switch of progesterone metabolism toward a four-fold to 10-fold increase in serum and urine concentration of sulfated metabolites, with an increased ratio of 3a-hydroxysteroid sulfates to 3b-hydroxysteroid sulfates, changes that were reversed after treatment with ursodeoxycholic acid. (4) Among other important steps in this research line, Glantz et al, in Sweden, reported similar changes in the pattern of progesterone metabolites in urine of ICP patients, with a reversal after ursodeoxycholic acid administration, correlating with an improvement in maternal pruritus (5) ; and Abu-Hayyeh et al also reported increased levels of progesterone sulfates in ICP patients studied in the United Kingdom. (6) Therefore, this metabolic pattern has been detected in ICP patients from different geographic locations and ethnic origins.…”
mentioning
confidence: 79%
“…Patients with these characteristics have been identified in several studies, being usually labeled as having pruritus gravidarum (PG), an enigmatic entity that does not carry the fetal risks of a genuine ICP. (5,(9)(10)(11) Table 1 summarizes clinical and biochemical data previously reported in patients with ICP and in normal pregnancies, (7) comparing them with a concurrent unreported cohort of patients with PG in whom pruritus appeared at the same gestational age but was slightly less severe than in patients with ICP. In three of these patients with PG, pruritus diminished spontaneously 1 week prior to delivery; and in another patient, pruritus disappeared in the final week of pregnancy, a phenomenon that was not observed in patients with a genuine ICP.…”
mentioning
confidence: 99%
“…Furthermore, progesterone metabolites are discussed as possible mediators of cholestatic pruritus and of particular interest in cholestasis of pregnancy. Treatment of ICP with ursodeoxycholic acid not only lowers levels of serum bile acids but also of steroid disulfated progesterone metabolites through increased hepatobiliary secretion, which is paralleled by improving pruritic symptoms [11].…”
Section: Specific Dermatoses Of Pregnancymentioning
confidence: 99%
“…Some studies have reported that UDCA administration also reduces maternal plasma concentrations of some PMS [9,10], and this has been related to the improved maternal hepatobiliary function [11]. During intra-uterine life, the placenta is essential for this function in the foetus.…”
Section: Introductionmentioning
confidence: 99%